Polyphenol rich fraction and uses thereof - Ismail, Amin; Kong, Kin Weng; Tan, Seok Tyug; Othman, Azizah; Ismail, Abdul Razak (2009)
The present invention discloses guava polyphenols rich fraction obtained from a guava tree. Another embodiment of the [present invention discloses uses of the guava polyphenols rich fraction as natural food ingredients and as antioxidant.